2016
DOI: 10.1080/13651501.2016.1229794
|View full text |Cite
|
Sign up to set email alerts
|

Predictors of short-term outcome variables in hospitalised female adolescents with eating disorders

Abstract: In EDs, diverse factors may predict different outcome variables.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
22
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 20 publications
(32 citation statements)
references
References 49 publications
2
22
0
Order By: Relevance
“…Only BMI at admission was associated with this clinical outcome. This is in line with findings from other authors (Agüera et al, 2015;Mekori et al, 2017) who reported that admission BMI was predictive of BMI at follow-up among patients with AN.…”
Section: Discussionsupporting
confidence: 93%
“…Only BMI at admission was associated with this clinical outcome. This is in line with findings from other authors (Agüera et al, 2015;Mekori et al, 2017) who reported that admission BMI was predictive of BMI at follow-up among patients with AN.…”
Section: Discussionsupporting
confidence: 93%
“…Mixed diagnoses Two studies of multimodal inpatient treatment were found which reported on weight gain during inpatient treatment for patients with mixed eating disorder diagnoses (Table 39). One study differentiated between patients with AN restricting type versus those with AN binge-purge type or BN [203], and the other differentiated between those with AN restricting type or AN binge-purge type versus those with BN or Eating Disorder Not Otherwise Specified binge-purge type (EDNOS-B/P) [193]. Multimodal treatment was provided in both studies but varied between studies.…”
Section: Multimodal Treatmentmentioning
confidence: 99%
“…We failed to identify any RCTs exploring outcomes of inpatient treatment specifically for pediatric AN, including atypical anorexia nervosa. We identified twenty studies (total n = 1091) describing inpatient treatment based on an integrative approach for AN, including psychiatric, medical, nutritional, and pharmacologic management, as well as individual, group and family therapy along with skilled nursing support [18][19][20][21][22][23][24][25][26][27][28][29][30][31][32][33][34][35][36][37]. None of these studies included control or comparison groups.…”
Section: Resultsmentioning
confidence: 99%
“…Three studies using an integrative approach (total n = 239) were included and reported on weight gain during inpatient treatment for patients with mixed ED diagnoses [9,28,30] (Table 2). The studies included in this [28,30].…”
Section: Inpatient Programs For Mixed Ed Diagnoses Weight Gainmentioning
confidence: 99%